2016
DOI: 10.1063/1.4953849
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of group-3 metal hexaboride nanoparticles by first-principles calculations

Abstract: LaB6 nanoparticles are widely used as solar control materials for strong near-infrared absorption and high visible transparency. In order to elucidate the origin of this unique optical property, first-principles calculations have been made for the energy-band structure and dielectric functions of R(III)B6 (R(III) = Sc, Y, La, Ac). On account of the precise assessment of the energy eigenvalues of vacant states in conduction band by employing the screened exchange method, as well as to the incorporation of the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 59 publications
1
9
0
1
Order By: Relevance
“…In terms of ε 2 (ω), LaB 6 absorbs weakly in the visible light region, and a high absorption is observed in the low-energy side including the near-infrared region. These characteristics are consistent with the measurements 3,8,10 and calculated values 18 reported in previous studies. For applications as a solar shielding material, ε 2 (ω) should have a large value in the near-infrared region and a small value in the visible region.…”
Section: ■ Results and Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In terms of ε 2 (ω), LaB 6 absorbs weakly in the visible light region, and a high absorption is observed in the low-energy side including the near-infrared region. These characteristics are consistent with the measurements 3,8,10 and calculated values 18 reported in previous studies. For applications as a solar shielding material, ε 2 (ω) should have a large value in the near-infrared region and a small value in the visible region.…”
Section: ■ Results and Discussionsupporting
confidence: 93%
“…The crystal structure of LaB 6 is shown in Figure 1 A previous study reported by our research group shows that the optical characteristics of LaB 6 can be reproduced quantitatively by considering the Drude term, which includes the effect of free electrons, and by calculating the effect of interband transitions using a hybrid calculation method that accurately reproduces the band gap. 18 Details are described in the Methods section.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This prohibition of certain transitions between metal-d and ligand-p orbitals further amplies the visible transparency, enabling it even when the conduction and valence bands overlap in specic directions, as occurs in LaB 6 . 21 The optical absorption of Cs-HTB nanoparticles is known large at both frequency ends of the visible region. On the blue side of the spectrum, the 3 2 is enlarged by band-edge interband transition; on the red side, strong absorption occurs by LSPR and polaronic electronic transition.…”
Section: Introductionmentioning
confidence: 99%
“…Ключевые слова: совместное осаждение, боротермическое восстановление, гексаборид лантана, диборид циркония. ВВЕДЕНИЕ Э втектические композиции в системах LnB 6 -MeB 2 (где Ln -лантаноиды, Me -переходные металлы IV-VI групп) обладают высоким уровнем термоэмиссионных [1-8] и физикомеханических свойств [6,[9][10][11][12][13][14], а также представляют потенциальный интерес вследствие выдающихся оптических характеристик гексаборидов РЗМ в ближней ИК-области спектра [15][16][17][18][19]. Благодаря высокой температуре плавления и способности в процессе окисления поверхностного слоя образовывать стабильные цирконаты и гафнаты со структурой пирохлора LaB 6 применяется в качестве добавок к ZrB 2 и HfB 2 при создании ультравысокотемпературных керамик (UHTCs), в частности в составе квазитройной системы ZrB 2 -SiC-LaB 6 [20].…”
unclassified